1979
DOI: 10.1056/nejm197901113000203
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal-Ulcer Disease Associated with Elevated Serum Pepsinogen I

Abstract: To delineate genetic factors involved in the pathogenesis of duodenal ulcer, serum pepsinogen I levels were determined by radioimmunoassay in two large kindreds with multiple members affected with duodenal ulcer. An elevated serum immunoreactive pepsinogen I concentration (greater than 100 ng per milliliter) segregated as an autosomal dominant trait in these families. Furthermore, 10 of 11 patients with clinical ulcer disease in these families had hyperpepsinogenemia. An elevated serum pepsinogen I concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
3

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(42 citation statements)
references
References 14 publications
1
38
0
3
Order By: Relevance
“…The human stomach expresses two isozymogens, PGI and PGII, with different biochemical and immunological properties (13). Histological studies based on immunohistochemistry using specific antibodies or in-situ hybridization have clearly identified cells that produce PGI and PGII (14)(15)(16) (17)(18)(19)(20)(21)(22)(23). It is important to note that, during the process of chronic atrophic gastritis, mucosal atrophy advances from the side of the pyloric gland towards the oral side, and that PGI levels and PGI/PGII ratios decrease with advancement in mucosal atrophy (18)(19)(20)23) (Fig.…”
Section: Pepsinogen Testingmentioning
confidence: 99%
“…The human stomach expresses two isozymogens, PGI and PGII, with different biochemical and immunological properties (13). Histological studies based on immunohistochemistry using specific antibodies or in-situ hybridization have clearly identified cells that produce PGI and PGII (14)(15)(16) (17)(18)(19)(20)(21)(22)(23). It is important to note that, during the process of chronic atrophic gastritis, mucosal atrophy advances from the side of the pyloric gland towards the oral side, and that PGI levels and PGI/PGII ratios decrease with advancement in mucosal atrophy (18)(19)(20)23) (Fig.…”
Section: Pepsinogen Testingmentioning
confidence: 99%
“…5% of women in the Caucasian western population are expected to have some form of ulcer disease during their lifetime. This unchanged trend is genetically programmed: 30-59% of ulcer patients have a positive family history in contrast to 5-15% of control persons (2)(3)(4)(5). DU and GU follow separate genetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The serum pepsinogen levels were highly elevated in the blood group 0 patients when compared with other blood group A, B and AB patients. According to Hanley's report 1 • the extent of peptic secretory cell mass is influenced by sex, by ABO blood genes, and the serum pepsinogen levels and probably reflects the size of the gastric secretory cell mass. Their experimental resultsis revealed that the gastric secretory cell mass is larger in group 'O' phenotypes than in group 'A' phenotypes.…”
Section: Discussionmentioning
confidence: 99%